Financial Performance and Sustainability in Malaysian Waqf Private Entity and Corporations - Mustafa Mohd Hanefah; Muhammad Iqmal Hisham Kamaruddin; Rosnia Masruki; Fuadah Johari; Kamarubahrin A.F. (Science and Engineering Research Support Society, 2024)
Indexed by ERA